Relationship Between Activities of Daily Living and Depression in Older Adults - Marzieh Mohamadzadeh; Vahid Rashedi; Mitra Hashemi; Vahidreza Borhaninejad (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: Physical disability to perform daily living activities is one of the major causes of depression in the elderly people. On the other hand, depression is associated with loss of interest in daily activities and lack of independence. The present study aimed to assess the relationship of depression with the ability to perform Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) in older adults in Iran. Methods & Materials: This cross-sectional study was performed on 148 elderly people aged ≥60 years who were selected by multi-stage cluster sampling method. Data were collected by using ADL, IADL, and 15-item Geriatric Depression Scale (GDS-15) questionnaires and were then presented by using descriptive statistics and analyzed by Chi-square test, Pearson correlation coefficient, and regression analysis. Results: Participants were 86 female (58.1%) and 62 male (41.9%); 109 (73.6%) aged 60-75 years, and the rest were older than 75 years; 71 (48%) had moderate or severe depression; 4(2.7%) and 61(41.2%) were dependent or in need of help performing ADL and IADL, respectively. Statistical analysis showed that depression has a significant negative correlation with ADL (r= -0.304, P<0.001) and IADL (r=-0.193, P>0.01); i.e. by increasing one of them, the depression decreases. Conclusion: The ability of the elderly people to perform ADL and IADL can be a good predictor of depression in them. With early assessment of their health and ability by health teams and family members, it is possible to prevent the development of their disability and depression.